Review: Early life predisposing factors for biting in pigs. (22nd August 2019) - Prunier, A.; Averos, X.; Dimitrov, I.; Edwards, S. A.; Hillmann, E.; Holinger, M.; Ilieski, V.; Leming, R.; Tallet, C.; Turner, S. P.; Zupan, M.; Camerlink, I.
Abstract : The pig industry faces many animal welfare issues. Among these, biting behaviour has a high incidence. It is indicative of an existing problem in biters and is a source of physical damage and psychological stress for the victims. We categorize this behaviour into aggressive and non-aggressive biting, the latter often being directed towards the tail. This review focusses specifically on predisposing factors in early life, comprising the prenatal and postnatal periods up to weaning, for the expression of aggressive and non-aggressive biting later in life. The influence of personality and coping style has been examined in a few studies. It varies according to these studies and, thus, further evaluation is needed. Regarding the effect of environmental factors, the number of scientific papers is low (less than five papers for most factors). No clear influence of prenatal factors has been identified to date. Aggressive biting is reduced by undernutrition, cross-fostering and socialization before weaning. Non-aggressive biting is increased by undernutrition, social stress due to competition and cross-fostering. These latter three factors are highly dependent on litter size at birth. The use of familiar odours may contribute to reducing biting when pigs are moved from one environment to another by alleviating the level of stress associated with novelty. Even though the current environment in which pigs are expressing biting behaviours is of major importance, the pre-weaning environment should be optimized to reduce the likelihood of this problem.